Oral Cavity and Candida albicans: Colonisation to the Development of Infection - Mrudula Patel (Pathogens, 2022)
Candida colonisation of the oral cavity increases in immunocompromised individuals which leads to the development of oral candidiasis. In addition, host factors such as xerostomia, smoking, oral prostheses, dental caries, diabetes and cancer treatment accelerate the disease process. Candida albicans is the primary causative agent of this infection, owing to its ability to form biofilm and hyphae and to produce hydrolytic enzymes and candialysin. Although mucosal immunity is activated, from the time hyphae-associated toxin is formed by the colonising C. albicans cells, an increased number and virulence of this pathogenic organism collectively leads to infection. Prevention of the development of infection can be achieved by addressing the host physiological factors and habits. For maintenance of oral health, conventional oral hygiene products containing antimicrobial compounds, essential oils and phytochemicals can be considered, these products can maintain the low number of Candida in the oral cavity and reduce their virulence. Vulnerable patients should be educated in order to increase compliance.